Students’ Self-Correction: A Strategy for Writing Improvement - Dahal, Betendra Kumar (Surkhet Journal, 2023)
The purpose of this action research is to find out why students are disinterested in writing and implement self-correction technique to motivate them in writing. I purposively selected the participants for this study consisting of 35 students of grade six studying in one of the schools in Surkhet valley. The study was based on Exploratory Action Research (EAR) with mixed-method approach in which I employed questionnaire, discussion and note-copy observation as the tools for data collection. After reviewing the data self-correction technique was taken into action. The result indicates that self-correction technique enables the students’ writing along with motivating and developing their interest in writing. This study encourages the teachers and ELT practitioners to conduct similar studies in other skills of language learning to explore and implement student-centered teaching strategies in the classrooms.